2020 International Conference on UK-China Emerging Technologies (UCET) 2020
DOI: 10.1109/ucet51115.2020.9205461
|View full text |Cite
|
Sign up to set email alerts
|

Human activity classification with radar signal processing and machine learning

Abstract: As the number of older adults increases worldwide, new paradigms for indoor activity monitoring are required to keep people living at home independently longer. Radar-based human activity recognition has been identified as a sensing modality of choice because it is privacy-preserving and does not require end-users compliance or manipulation. In this paper, we explore the robustness of machine learning algorithms for human activity recognition using six different activities from the University of Glasgow datase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 13 publications
0
26
0
Order By: Relevance
“…In this work, spectrograms are used to capture the various velocity patterns of different body parts in human movements. However, recent works [17], [82], [83] have shown that combining multidomain information for HAR can also be advantageous, e.g., combining the RD, DT, CVD, and RT information.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, spectrograms are used to capture the various velocity patterns of different body parts in human movements. However, recent works [17], [82], [83] have shown that combining multidomain information for HAR can also be advantageous, e.g., combining the RD, DT, CVD, and RT information.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, the most common methods of human activity detection are visionbased detection like using cameras and sensor-based detection such as using wearable sensors, radar and smartphone sensors [3,4]. Among all the methods, radar technology outperforms the other for the following aspects [5][6][7][8]. Environmental insensitivity: radar detection is not influenced by harsh light; Contactless Sensing: users do not need to wear or connect with any devices, which provides a high capability of comfort and convenience; Privacy Protection: radar technology collects human activity data without showing their actual images, ensuring the privacy of individuals.…”
Section: Contextmentioning
confidence: 99%
“…As machine learning developed, many researchers began to directly consider the grayscale of RGB images of spectrograms as features. Then, convolutional neural networks derived from vision-based classification were applied to those images for classification [3][4][5][6][7]10,22]. Compared with the conventional hand-crafted feature extraction approaches, the use of deep learning technology can increase the accuracy in classification.…”
Section: Micro-doppler Maps (Spectrograms)mentioning
confidence: 99%
“…To the first category belong, studies where handcrafted features are extracted from the pre-processed radar data and then used together with supervised Machine Learning algorithms. For instance, studies such as [11]- [13] used handcrafted features and machine learning algorithms (e.g. Support Vector Machine, SVM) to classify different human activities, intended as individual motions performed by human subjects (e.g., walking, sitting still, boxing, and so on).…”
Section: Introductionmentioning
confidence: 99%